2022
DOI: 10.1016/j.jdent.2022.103948
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of single use plastics waste generated in clinical dental practice and hospital settings

Abstract: This is a repository copy of Quantification of single use plastics waste generated in clinical dental practice and hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A recent study conducted in the UK has identified a mean of twentyone (n=21) SUP items utilised in every routine adult primary care dental procedure, with a mean mass of 354g per procedure. This figure can be extrapolated to a conservative estimate of approximately two billion dental SUP items per year (14.4 tonnes) [38]. The additional PPE required during the COVID-19 pandemic increased this figure to approximately 2.4 billion SUP items (27 tonnes) in the UK.…”
Section: Awareness and Challengesmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent study conducted in the UK has identified a mean of twentyone (n=21) SUP items utilised in every routine adult primary care dental procedure, with a mean mass of 354g per procedure. This figure can be extrapolated to a conservative estimate of approximately two billion dental SUP items per year (14.4 tonnes) [38]. The additional PPE required during the COVID-19 pandemic increased this figure to approximately 2.4 billion SUP items (27 tonnes) in the UK.…”
Section: Awareness and Challengesmentioning
confidence: 94%
“…The additional PPE required during the COVID-19 pandemic increased this figure to approximately 2.4 billion SUP items (27 tonnes) in the UK. Further studies of this type are required in alternative settings to obtain a clear baseline and to help inform remediation strategies [32,38,45]. Recycling as a basis for a business model is a significant challenge that needs resolving.…”
Section: Awareness and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is broad agreement that stakeholders in the oral health care sector could potentially make significant reductions in the volumes of waste generated, most notably from modifying manufacturing processes, packaging, and the high prevalence use of single-use products (mostly plastic and personal protective equipment). 6 …”
Section: Rationalementioning
confidence: 99%
“…There are plastic materials that, due to their versatility, are widely used; however, the proper management of their recycling is a longstanding problem (Grodzińska-Jurczak et al, 2022). Plastics such as LDPE are widely used for the manufacture of plastic bags (Martin et al, 2022), as the bags given to us in supermarkets, when shopping, are commonly made of LDPE because it is the most common way of transporting any goods (Gómez & Escobar, 2022).…”
Section: Introductionmentioning
confidence: 99%